ACCEPTABILITY AND NUTRIENTS CONTENT (VITAMIN B12 AND FOLIC ACID) OF SUBTITUTED SNACK BAR WITH PURPLE SWEET POTATO (IPOMOEA BATATAS L.) ENRICHED WITH NUTRITIONAL YEAST AS HEALTHY VEGAN FOOD - Achmad Maralda Ainin Ghifari (Universitas Airlangga, 2021)
Vegan are group of people who have high risk of megaloblastic anaemia because of vitamin B12 and folic acid defi ciency. Purple sweet potato (Ipomoea Batatas L.) and nutritional yeast are rich vitamin B12 and folic acid, therefore can be formulated into healthy food, such as snack bar for vegan. The purpose of this study is to determine the eff ect of purple sweet potato substitution and nutritional yeast addition on acceptability and availability of vitamin B12 and folic acid of snack bar. The type of research of formulation was true experimental design (Complete Randomize Design) with 1 formula control and 2 modifi ed formula. This research was carried out for 3 months (December 2018-March 2019) in Nutrition Laboratory Universitas Airlangga. The panelists are 38 people who affi liated with vegan community Yayasan Buddha Maitreya Surabaya. Statistical analysis used Kruskall Wallis test and Mann Whitney test with 5% signifi cance level. The results of organoleptic test showed that the most preferred formula by panelists was F2 with an average value of 3,6. There are diff erences in terms of smell characteristic (p=0.017) and taste characterictic (p=0.021). F2 have the highest content of vitamin B12 and folic acid, which are 1.58 mcg and 1,62 mcg, respectively, for 50 gram snack bar. The study showed that the best optimization (acceptability and nutrient content) in formula is F2 (substitution of 20% of purple sweet potato and addition 9 g of nutritional yeast). Therefore, snack bar with purple sweet potato substitution and nutritional yeast enrichment is feasible as an alternative healthy snack for vegan.